2005
DOI: 10.1529/biophysj.104.057307
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Enzyme Activity in Lipid Signaling Pathways Related to Substrate Reordering

Abstract: The static fluid mosaic model of biological membranes has been progressively complemented by a dynamic membrane model that includes phospholipid reordering in domains that are proposed to extend from nanometers to microns. Kinetic models for lipolytic enzymes have only been developed for homogeneous lipid phases. In this work, we develop a generalization of the well-known surface dilution kinetic theory to cases where, in a same lipid phase, both domain and nondomain phases coexist. Our model also allows under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…Meanwhile, the interaction between dietary flavonoids and trace minerals may affect metal homeostasis in a structure-specific fashion. Since fluid properties of biological membranes were essential for numerous cell functions including solute transport and membraneassociated enzymatic activities [27], it is possible that even mild alterations produced by the lipophilic structures of flavonoids on membrane fluidity could cause aberrant function and changes in membrane permeability [28]. The D-ring hydroxyl groups of the flavonoid structure occupy the first coordination sphere around metal ion to form a diolate combination ring, while B-ring hydroxyl groups have weak interactions with metal ions [29].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the interaction between dietary flavonoids and trace minerals may affect metal homeostasis in a structure-specific fashion. Since fluid properties of biological membranes were essential for numerous cell functions including solute transport and membraneassociated enzymatic activities [27], it is possible that even mild alterations produced by the lipophilic structures of flavonoids on membrane fluidity could cause aberrant function and changes in membrane permeability [28]. The D-ring hydroxyl groups of the flavonoid structure occupy the first coordination sphere around metal ion to form a diolate combination ring, while B-ring hydroxyl groups have weak interactions with metal ions [29].…”
Section: Discussionmentioning
confidence: 99%
“…Since fluid properties of biological membranes were essential for numerous cell functions including cell growth, solute transport, signal transduction, and membrane-associated enzymatic activities (Sunshine and McNamee, 1994; Salinas et al, 2005;Balint et al, 2005), it is possible that even mild alterations in membrane fluidity could cause aberrant function and set in motion pathological processes (Cooper, 1977;de Gómez Dumm et al, 2001). However, it should be noted that changes in membrane fluidity need not necessarily render them 'leaky' since transport or translocation of compounds across cell membranes is a different physiological process, which is not directly related to the horizontal fluidity of the membrane.…”
Section: +mentioning
confidence: 99%
“…Similarly to the kinetic models for substrate distributions in one homogeneous lipid phase (Carman et al 1995;Hendrickson and Dennis 1984) or two homogeneous lipid phases (Salinas et al 2005), we assume that:…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This led us to propose a kinetic theory to reveal the effect of substrate reordering in two phases or domains on phospholipase enzyme kinetics (Salinas et al 2005). We found that the predicted kinetics depended on the model chosen to describe the interaction of the enzyme with the membrane:…”
Section: Introductionmentioning
confidence: 99%